A baseline study on trace element based sediment pollution and potential ecological risk of reef sediments of Musal, Manoli and Manoli putti Islands, Gulf of Mannar, India. (August 2018) - Saravanan, P.; Pradhap, D.; Krishnakumar, S.; Silva, Judith D.; Vidyasakar, A.; Sackaria, Merin; Godson, Prince S.; Arumugam, K.; Magesh, N.S.
Abstract: The aim of the present study is to assess the baseline level of the trace element, sediment pollution and potential ecological risk of reef associated sediments of Musal, Manoli and Manoli putti Islands, Gulf of Mannar, India. The grain size distribution of the sediments is chiefly controlled by corals and broken shell debris. The distribution of lithoclastic fractions and element concentration are most probably derived from longshore sediment transport and fluvial process from nearby mainland. The enrichment of organic matter is chiefly controlled by mangrove litters and sea grasses. The concentration of lead in the marine sediments is subjected to sediment matrix, vicinity of the local pollutant sources and distance from the mainland coast. The ecological risk assessment clearly reveals that the sediments belong to the low risk category. Highlights: The present study was carried out to assess the ecological risk status of the Musal, Manoli and Manoli putti Islands. The lithic fragments in the reef sediments are controlled by longshore sediment transport and fluvial process. The distribution of the elements is accumulated less than crustal average value. The ecological study of reef associated sediments indicates that the sediments belong in the low risk category.